Application of carbon nanomaterials in plant biotechnology. (2020) - Majeed, Neelofar; Panigrahi, Kishore C.S.; Sukla, Lala Behari; John, Riffat; Panigrahy, Madhusmita
Abstract: Carbon nanomaterials are increasingly used in biomedical engineering and medicinal chemistry in recent years due to their unique structural and mechanical properties. Because of their highly tuneable physical properties, carbon nanotubes are most produced for their applicability in electronics, optics, nanomedicine, solar cells, high energy efficient renewable energy production, remediation, biosensors for pollutants and degradation of contaminants. Application of carbon nanotubes in agriculture and plant research is still a recent development in nanobiotechnology. Despite the potential application of carbon nanotubes for delivering cargo such as proteins, nucleic acids, and drugs for their targeted delivery to cells and organs, inhibition of cell proliferation, induced plasma membrane hyper polarization, oxidative stress in various in vitro mammalian cell studies have raised special concern about their toxicity in animals. This review aims not only to have a brief introduction of types and structures of nanotubes, but also through the detailed descriptions of its applications as biosensors, molecular carriers, in environmental applications, agricultural applications and toxicity issues it will deliver the update knowledge and future perspectives of carbon nano research.